2013
DOI: 10.1590/s1516-89132013005000010
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Antimicrobial Activity of Glucose Oxidase from Aspergillus niger EBL-A and Penicillium notatum

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 23 publications
1
16
0
Order By: Relevance
“…Glucose oxidase has been extensively researched as an antimicrobial agent to be used in human medicine and food preservation [32]. Despite this remarkable success, the share of GOD as biofungicides has not been reported yet.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Glucose oxidase has been extensively researched as an antimicrobial agent to be used in human medicine and food preservation [32]. Despite this remarkable success, the share of GOD as biofungicides has not been reported yet.…”
Section: Discussionmentioning
confidence: 99%
“…However, it could presumably be attributed to the fact that GOD treatment may damage cell membrane and leakage of intracellular proteins and sugars, thus inhibiting the fungal phytopathogen [33]. GOD has a versatile ability to inhibit the growth of microbes by naturally produced hydrogen peroxide [32]. It was largely reported in the literature that H 2 O 2 , at very low concentrations (at the mg level), inhibits the growth of microorganisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result of the antimicrobial effect, glucose oxidase can be seen as an indirect agent for food storage and packaging, also improving the shelf-life of foods because this enzyme shows impressive talent to inhibit the growth of microbes thanks to the self-produced hydrogen peroxide after glucose catalyzing. Moreover, some evidence from the scientific area has been revealed that also gluconic acid, a subreaction product, is responsible for the antimicrobial activity [11,20]. Actually, it has known that the level of glucose oxidase in honey is not stipulated by any standard committee as a quality criterion.…”
Section: Glucose Oxidase Values Of Honey Samplesmentioning
confidence: 99%
“…Corn steep liquor is a by-product of the corn starch production process; in some industries, like the case in this study, it is considered an effluent. However, in some studies, it has been used as a relatively inexpensive source of nutrients to make up the culture medium of various microorganisms, such as bacteria and yeast [9][10][11][12][13][14].…”
Section: Introduction mentioning
confidence: 99%